Response of goats to intramuscular vaccination with heat-killed Mycobacterium bovis and natural challenge. (October 2018) - Roy, Álvaro; Risalde, María A.; Bezos, Javier; Casal, Carmen; Romero, Beatriz; Sevilla, Iker; Díez-Guerrier, Alberto; Rodríguez-Bertos, Antonio; Domínguez, Mercedes; Garrido, Joseba; Gortázar, Christian; Domínguez, Lucas
Highlights: Heat-inactivated M.bovis reduces the lesions in goats naturally exposed to M.caprae . Natural challenge is a realistic model to evaluate the efficacy of TB vaccines. Goats are an experimental model for TB vaccine development. Abstract: Caprine TB causes chronic disease with severe economic and health consequences. We assessed the effect of intramuscularly administered heat-inactivated Mycobacterium bovis ( M. bovis ) on 20 kid goats (10 vaccinated, 10 controls), naturally exposed to M. caprae through close contact with infected goats. At necropsy, visible TB-compatible lesions were recorded in all animals with the exception of 1 control and 2 vaccinated goats. The median of the total lesion score was 9 (IQR 3–13.5) and 5 (IQR 3–6.75) in control and vaccinated goats, respectively (median lesion reduction 44.4%, p = 0.224). The lung lesions of the vaccinated goats were restricted to the caudal lobes, while 6 controls had additional lung lobes affected ( p = 0.01). The median lung lesion score reduction in vaccinated goats was 100%; however, this reduction was not significant ( p = 0.124), possibly due to the low sample size. Regarding the abdomen, only one vaccinated goat presented visible lesions compared to three goats in the control group. The results provide further evidence of the potential of heat-inactivated M. bovis for controlling TB in different host species, including ruminants.